The Developmental Implications of the Use of Reproductive Technologies for Transgender People: A Comparative Cross-Section Protocol - Mamou, Grégor; Lagrange, Chrystelle; Mendes, Nicolas; Wielart, Joy; Poirier, Fanny; Medjkane, François; Brunelle, Julie; Drouineaud, Véronique; Rosenblum, Ouriel; Gründler, Nouria; Ansermet, François; Falissard, Bruno; et al. (Frontiers in Psychiatry, 2020)
Background Today, individuals and couples with fertility issues can use advances in biomedical technologies to conceive. Transgender persons also benefit from these advances and can not only actualize their self-identified gender identities but also experience parenthood. These strategies for persons to self-actualize and to access parenthood have improved the condition of transgender persons. However, some may question the welfare of the offspring because such transfamily forms are often confusing to many. The sparse research on the psychological well-being of children of transgender people is reassuring. However, the limited empirical research justifies more studies to be conducted with an evidence-based methodology to assess whether these new methods of parenting have any adverse impact on children. Aims The current report details the protocol we built to compare cognitive development, mental health, gender identity, quality of life, and family dynamics in children of transgender fathers and donor sperm insemination (DSI) and two control groups matched for age and gende typically developing (TD) children and children from cisgender parents and DSI. Hypothesis To calculate sample sizes, we hypothesize no significant difference between groups. Subjects and Methods Since 2008, married couples that include a transgender father have been able to access DSI and have started conceiving children in France. They are always invited to participate in research to assess their children's well-being. To date, the cohort includes 53 children in 37 families. We propose to carry out a cross-sectional comparative study exploring cognitive development with the Brunet–Lézine Psychomotor Development Scale or Wechsler's Intelligence Scales according to age; mental health with the Child Behaviour Checklist; gender identity with the Gender Identity Interview for Children; quality of life with the KIDSCREEN and the Adolescent Coping Questionnaire; and family dynamics with the Parental Bonding Instrument, the Inventory of Parent and Peer Attachment, the Five-Minute Speech Sample, and Corman's Family Drawing Test. To assess possible subtle differences between children's family drawings, we will use a generalization of the “lady-tasting-tea” procedure to link qualitative and quantitative approaches in psychiatric research. Twenty raters [four child and family psychoanalysts (CHILDPSY), four adult psychiatrists (ADUPSY), four biologists working in assistive reproduction technology (BIOL), four endocrinologists working with transgender individuals (ENDOC), and four students (STUD)] will be randomly shown the drawings and asked to blindly classify them using a Likert scale according to whether the child has a transgender father. Statistical Analysis After testing normality, comparisons between the three groups will be performed with appropriate statistical tests (Kruskal–Wallis, ANOVA, Chi2 or Fisher's exact test). For the “lady-tasting-tea” procedure, we will use a permutation test. Ethics The study protocol has been approved by the CERES (Comité d'Ethique de Recherche en Santé) of Paris 5 University. Registration number is 2015/31.